Electrode, anode for water electrolysis, electrolysis cell, and method for producing hydrogen
Patent Information
- Application Number
- JP2021052324
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-03-25
AI Technical Summary
【0012】 本発明によれば、再利用を前提としてゼロギャップ型電解セルにて使用可能な、低い酸素過電圧を有する電極、水電解用陽極、及びこの水電解用陽極を備えた水電解セルを得られる。
Smart Images

Figure 0007634400000003 
Figure 0007634400000004 
Figure 0007634400000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode, an anode for water electrolysis, a bipolar electrolytic cell using the anode for water electrolysis, and a method for producing hydrogen using the anode for water electrolysis. [Background technology]
[0002] In recent years, CO 2 Hydrogen produced using renewable energy has been attracting attention as a clean energy source that can solve problems such as global warming caused by renewable energy and dwindling reserves of fossil fuels. Hydrogen production using renewable energy requires low costs comparable to those of conventional hydrogen production by reforming fossil fuels. Therefore, hydrogen production using renewable energy requires high levels of energy efficiency and inexpensive equipment that could not be achieved with conventional technologies.
[0003] One method for producing hydrogen that can meet the above requirements is electrolytic decomposition of water (water electrolysis). For example, several ideas have been proposed for producing hydrogen by water electrolysis using power generation from natural energies such as wind power or solar power, and storing or transporting the hydrogen.
[0004] In water electrolysis, oxygen is generated at the anode and hydrogen is generated at the cathode by passing an electric current through the water. The main cause of energy loss in electrolysis is the overvoltage of the anode and cathode. Reducing this overvoltage makes it possible to produce hydrogen efficiently. In particular, the overvoltage of the anode is higher than that of the cathode, and research and development into reducing the overvoltage of the anode is being widely conducted.
[0005] Among oxides having a perovskite structure, materials with high oxygen generating capacity are known, and they have attracted attention as anode materials for water electrolysis (Non-Patent Document 1). In order to use an oxide having a perovskite structure as an anode for alkaline water electrolysis, there is a method of forming an oxide layer on the surface of a conductive substrate. For example, Patent Document 1 discloses an anode for water electrolysis that has low oxygen overvoltage and high durability by forming a metal oxide layer having a high content of perovskite oxide in the crystalline component on the surface of a nickel porous substrate, and a water electrolysis device using the anode. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2018 / 155503 [Non-patent literature]
[0007] [Non-Patent Document 1] Science, 2011, 334, 1383 Summary of the Invention [Problem to be solved by the invention]
[0008] The anode described in Patent Document 1 exhibits high durability against long-term current application, but it has been found that the electrode recovered after current application in a zero-gap electrolytic cell has the problem of exhibiting high overvoltage.
[0009] The present invention has been made in consideration of the above problems, and has an object to provide an electrode having a low overvoltage for oxygen generation after current recovery in a zero-gap electrolytic cell, an anode for water electrolysis, a bipolar electrolytic cell using the anode for water electrolysis, and a method for producing hydrogen using the anode for water electrolysis. [Means for solving the problem]
[0010] The present inventors have conducted extensive research and experiments to solve the above problems. As a result, they have discovered a LaNi alloy having a specific structure at the interface with the substrate. x M y O 3-z The inventors have found that an electrode on which a layer is formed has a low overvoltage for oxygen generation after current recovery in a zero-gap electrolysis cell and can be used as an anode for water electrolysis on the premise of reuse, thereby completing the present invention.
[0011] That is, the present invention is as follows. [1] LaNi x Nb y O 3-z (x+y is 0.8 to 1.2, y is 0 to 0.2, z is -0.5 to 0.5), and the nickel substrate and LaNi x Nb y O 3-z An electrode, characterized in that at an interface between the layers, a ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) is 1.5 or more and 3 or less. [2] The aforementioned LaNi x Nb y O 3-z The electrode according to [1], wherein the layer has a thickness of 60 μm or more and 100 μm or less. [3] The electrode according to [1] or [2], wherein y is 0.001 or more and 0.15 or less. [4] An electrolytic cell, comprising the electrode according to any one of [1] to [3] as an anode. [5] A method for producing hydrogen by electrolyzing alkali-containing water in an electrolytic cell, the electrolytic cell having at least an anode and a cathode, the anode having a LaNi x Nb y O 3-z (x+y is 0.8 to 1.2, y is 0 to 0.2, z is -0.5 to 0.5), and the nickel substrate and LaNi x Nb y O 3-zA method for producing hydrogen, characterized in that at an interface between layers, the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) is 1.5 or more and 3 or less. Effect of the Invention
[0012] According to the present invention, it is possible to obtain an electrode having a low oxygen overvoltage, an anode for water electrolysis, and a water electrolysis cell including the anode for water electrolysis, which can be used in a zero gap-type electrolysis cell on the premise of reuse. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a side view showing an example of an entire electrolytic cell including an electrolytic cell having the electrode of the present embodiment as an anode. [Diagram 2] FIG. 2 is a diagram showing a cross section of the inside of an electrolytic cell of an electrolytic cell including an electrode of the present embodiment as an anode, the electrolytic cell being enclosed in a dashed rectangular frame in FIG. [Diagram 3] FIG. 1 is a diagram showing an outline of an electrolysis device used in Examples and Comparative Examples. [Figure 4] FIG. 1 is a diagram showing an outline of a bipolar electrolytic cell used in an electrolysis test. [Diagram 5] 1 is an example of a cross-sectional photograph of an electrode. [Figure 6] This is an example of an image of a 100 μm square area cut out from FIG. 5. [Figure 7] This is an image of the interface extracted from Figure 6 and processed with thinning. [Figure 8] 8 is an image of the extension length from one end of the interface in FIG. 7 to the other end. [Figure 9] This is an image of the straight-line distance from one end of the interface to the other in Figure 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the following present embodiment is an example for explaining the present invention, and is not intended to limit the present invention. Furthermore, the present invention can be modified in various ways without departing from the gist of the present invention.
[0015] (electrode) In this embodiment, the electrode has at least a nickel base material. The nickel base material is a base material made of nickel or a material mainly composed of nickel. Examples of materials mainly composed of nickel include nickel-based alloys such as Monel, Inconel, and Hastelloy. The shape of the nickel base material may be a flat plate, or a porous body having a large number of holes. Specific shapes of the porous body include expanded metal, punched metal, plain weave mesh, foam metal, or shapes similar thereto. Among these, expanded metal is preferred, and the dimensions are not particularly limited. However, in order to achieve both an increase in the amount of gas generated due to an increase in the electrolysis surface area and efficient removal of the gas generated by electrolysis from the electrode surface, and from the viewpoint of mechanical strength, it is preferable that the center-to-center distance (SW) in the short direction of the mesh is 2 mm or more and 5 mm or less, the center-to-center distance (LW) in the long direction of the mesh is 3 mm or more and 10 mm or less, the thickness is 0.2 mm or more and 2 mm or less, and the opening ratio is 20% or more and 80% or less. More preferably, SW is 3 mm or more and 4 mm or less, LW is 4 mm or more and 6 mm or less, the thickness is 0.8 mm or more and 1.5 mm or less, and the opening ratio is 40% or more and 60% or less.
[0016] In this embodiment, the nickel base material is preferably sandblasted. The material of the abrasive used in the sandblasting process may be any known abrasive such as brown fused alumina, carborundum, or white fused alumina, but white fused alumina is preferably used from the viewpoint of chemical stability. In addition, when the grit of the abrasive is 40 or more and 220 or more, it is preferable to use the abrasive, since it is easy to set the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) to 1.5 or more and 3 or less. After the nickel base material has been subjected to sandblasting, it is preferable to remove residual abrasives by etching with an acid or the like.
[0017] In this embodiment, LaNi x Nb y O 3-z (x+y is 0.8 to 1.2, y is 0 to 0.2, z is -0.5 to 0.5). x Nb y O 3-z is deposited directly on the nickel substrate, x Nb y O 3-z The nickel substrate and the LaNi x Nb y O 3-z An interface may be formed between the layers. In this embodiment, high oxygen generating capacity can be realized by disposing Ni in at least a part of the B site of the metal oxide having a perovskite structure. Furthermore, disposing Nb in the B site together with Ni is preferable because it can provide a lower oxygen generating overvoltage after current recovery in a zero gap electrolytic cell. From the viewpoint of imparting a low overvoltage for oxygen generation after current recovery in a zero-gap electrolytic cell, x+y is 0.8 or more and 1.2 or less, more preferably 0.8 or more and 1.05 or less, and even more preferably 1.0 or more and 1.05 or less. y is 0 or more and 0.2 or less, preferably 0.001 or more and 0.15 or less, and more preferably 0.002 or more and 0.05 or less. z is -0.5 or more and 0.5 or less. In the present invention, z is determined by the composition ratio 3-z of O, which is calculated so that the valence balance of the composition formula is balanced, with La being trivalent, Ni being trivalent, Nb being pentavalent, and O being -2 valent. For example, in the composition formula LaNi x Nb y O 3-z If x = 0.9 and y = 0.1, then the relationship 3-z = (3+3×0.9+5×0.1) / 2 gives us z = -0.1. On the substrate, LaNix Nb y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0 or more and 0.2 or less, z is -0.5 or more and 0.5 or less) can be used to form a LaNi x Nb y O 3-z The layer is peeled off and dissolved in aqua regia, and the composition is analyzed by ICP-AES (inductively coupled plasma atomic emission spectroscopy). x Nb y O 3-z A method of peeling off the layer and analyzing the composition using an X-ray fluorescence analyzer, and a method of analyzing the LaNi x Nb y O 3-z This can be confirmed by a known method such as SEM-EDX analysis of the layer.
[0018] In this embodiment, the nickel substrate and LaNi x Nb y O 3-z The third characteristic is that the ratio of (extended length from one end of the interface to the other end) / (straight-line distance from one end of the interface) at the interface between the layers is 1.5 or more and 3 or less. "Extended length from one end of the interface" refers to the length when tracing along the line that constitutes the interface from one end of the line to the other end of the line. Also, "straight-line distance from one end of the interface to the other end" refers to the straight-line distance between both ends (one end and the other end) of the line that constitutes the interface. In this embodiment, the ratio of (extension length from one end of the interface to the other end) / (straight-line distance from one end of the interface) is calculated by embedding a small piece of the electrode in epoxy resin, cutting and polishing it to create a cross-sectional observation sample, cutting out an image for extracting the interface from a backscattered electron image observed with an electron microscope at a magnification of 500 times with a field of view width set to 100 μm, extracting the interface by processing the cut-out image using image processing software, determining the extension length from one end of the interface to the other end and the straight-line distance from one end of the interface to the other end in the cut-out image, and calculating the ratio. When the substrate is bent, the cross-sectional photograph is taken while avoiding the peaks (convex parts) and valleys (concave parts) of the bend. The 100 μm field of view for extracting the interface is set so that the interface is connected from the right end to the left end within the region and is never interrupted by the top, bottom, left, or right ends of the set portion. When cutting out the image, it is preferable to cut out an image having a height of 100 μm and a width of 100 μm, which is 100 μm square. By cutting out in this way, the linear distance from one end of the interface to the other end falls within the range of approximately 120±20 μm, making it easy to cut out the image. When processing an image, it is preferable to perform an appropriate filtering process in order to remove noise. A specific method for image processing will be described later in the embodiments.
[0019] The present inventors have developed a LaNi x Nb y O 3-z The nickel substrate and LaNi x Nb y O 3-z It was surprisingly found that an electrode in which the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) is 1.5 to 3 inclusive at the interface between the layer has a low overvoltage for oxygen evolution after current recovery in a zero-gap electrolysis cell. The reason for this is unclear, but x Nb y O 3-z This is believed to be because increasing the roughness of the interface between the layers creates an anchor effect, resulting in adhesion and suppressing peeling of the electrode catalyst from the substrate interface due to physical or chemical shocks, such as when washing with pure water during recovery after energization or when removing the electrode catalyst from the diaphragm or rib during disassembly of the zero gap structure. In order to reduce the overvoltage of oxygen generation after current recovery in a zero-gap electrolysis cell, the nickel substrate and LaNi x Nb y O 3-z The ratio of (extended length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) at the interface between the layers is preferably 1.6 to 2.8, more preferably 1.7 to 2.6. In this embodiment, LaNi x Nby O 3-z The thickness of the layer was determined by observing the cross-sectional observation sample used to calculate the ratio (extension length from one end of the interface to the other end) / (straight-line distance from one end of the interface) with an electron microscope, and averaging the thicknesses of the metal oxide layer at five points.
[0020] LaNi x Nb y O 3-z The thickness of the layer is preferably 60 μm or more and 100 μm or less from the viewpoint of reducing the overvoltage of oxygen generation after current recovery. If it is 60 μm or more, the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) is likely to be 1.5 or more. If it is 100 μm or less, the electrode preparation becomes easy, which is preferable from the viewpoint of productivity. When the electrode is prepared by the dip coating method described later, dissolution and reprecipitation of the calcined body occurs due to the acidic coating liquid during repeated coating, drying, and calcination, and as a result, LaNi x Nb y O 3-z The thickness of the layer tends to increase in the cross-sectional direction, and is more preferably from 65 μm to 95 μm, and further preferably from 70 μm to 85 μm.
[0021] The electrode of the present embodiment can be put to practical use as an anode for water electrolysis, and it is possible to provide an electrolytic cell for water electrolysis using the electrode of the present embodiment as an anode, and a method for producing hydrogen using the anode for water electrolysis. Water containing an alkali may be used for water electrolysis.
[0022] (Electrode Preparation Method) The electrode of this embodiment is prepared by applying an aqueous solution (coating solution) containing metal salts of La, Ni, and Nb to a substrate, drying and pre-firing the solution, and depositing a predetermined weight of LaNi x Nb y O 3-z The precursor can be prepared by forming the precursor and then subjecting it to main calcination.
[0023] The metal salt may be a water-soluble salt such as a nitrate, oxynitrate, chloride, oxalate, tartrate, acetate, sulfate, etc. The metal salt may be either anhydrous or hydrated. For La, Ni, and Nb, a water-dispersible sol of an oxide or hydroxide may be used instead of a metal salt. As the metal salt of Nb, it is preferable to use niobium oxalate or ammonium niobium oxalate from the viewpoint of solubility. In particular, when nitrates as metal salts of La and Ni and ammonium niobium oxalate as a salt of Nb are added to the coating solution, the pH of the coating solution is lowered, and the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) is likely to be 1.5 or more with a relatively small number of repeated coating, drying, and pre-baking cycles, which is preferable. For example, the composition LaNi 0.999 Nb 0.001 O 3.005 The pH of the coating solution with a concentration of 0.2 mol / kg of solvent is about 3.5. Adding organic ligands such as amino acids such as glycine, and carboxylic acids such as oxalic acid and tartaric acid to the coating solution makes the LaNi alloy highly resistant to high-temperature alkali. x Nb y O 3-z This is preferable from the viewpoint of facilitating the preparation of the above-mentioned compound. In particular, when a coating solution in which glycine and a metal nitrate are dissolved is used, it becomes easy to prepare an electrode having a low overvoltage for oxygen generation after current recovery in a zero-gap electrolytic cell, and therefore glycine is a preferred organic ligand.
[0024] The concentration of the aqueous solution containing metal salts of La, Ni, and Nb is LaNi x Nb y O 3-zThe standard molar concentration is preferably 0.1 mol / kg or more and 4 mol / kg or less. At 0.1 mol / kg or more, electrodes can be prepared with fewer coatings. At 4 mol / kg or less, metal salts and organic ligands are easily dissolved, which is preferable from the viewpoint of productivity of the coating solution. More preferably, it is 0.2 mol / kg or more and 2.0 mol / kg or less, and even more preferably, it is 0.2 mol / kg or more and 1.0 mol / kg or less.
[0025] After the coating liquid is applied to the substrate, the drying temperature is preferably 50° C. or higher and 200° C. or lower. If the temperature is 50° C. or higher, the drying is completed within 3 minutes to 1 hour, which is preferable from the viewpoint of productivity. If the temperature is 200° C. or lower, the cooling time of the substrate after drying is short, which is preferable from the viewpoint of productivity. The method of applying the coating solution to the substrate is preferably a dip coating method in which the substrate is completely immersed in the coating solution. When coating is performed by the dip coating method, an excess of the acidic coating solution repeatedly comes into contact with the substrate, and reactions such as dissolution by the acidic coating solution occur repeatedly on the nickel substrate surface, so that the nickel substrate and LaNi x Nb y O 3-z It is easy to make the ratio of (extension length from one end of the interface to the other end) / (straight-line distance from one end of the interface) at the interface between the layers equal to or greater than 1.5. When immersing the substrate in the coating solution, if the substrate is tilted and slowly immersed, it is possible to completely immerse the substrate without forming air bubbles. In addition, the voids in the metal oxide layer (calcined layer) formed on the substrate surface are completely replaced by the coating solution, so that the nickel substrate and LaNi x Nb y O 3-z This makes it easy to set the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) at the interface between the layers to 1.5 or more, which is preferable. In addition, by completely immersing the substrate and then holding it in the coating solution for 5 seconds or more, the nickel substrate and LaNi x Nb y O 3-zThis makes it easy to set the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) at the interface between the layers to 1.5 or more, which is preferable. The temperature for pre-baking the dried substrate is preferably 300° C. to 500° C. If it is 300° C. or higher, the pre-baking can be completed within 3 minutes to 1 hour, which is preferable from the viewpoint of productivity. If it is 500° C. or lower, the cooling time of the dried substrate is shortened, which is preferable from the viewpoint of productivity. Coating, drying, and pre-firing are performed to obtain the desired LaNi x Nb y O 3-z To adjust the amount of electrode attached, the process may be repeated, and the more times the process is repeated, the larger the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) tends to be, which is preferable. The process is preferably repeated 50 times or more, and more preferably 60 times or more.
[0026] The temperature for the main firing can be from 500° C. to 1000° C., but firing at 750° C. or higher is preferable. When firing at 750° C. or higher, the firing time is from 10 minutes to 24 hours, and the ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) can be controlled to 1.5 or more, making it possible to prepare an electrode with low overvoltage for oxygen generation after current recovery in a zero-gap electrolytic cell, which is preferable from the viewpoint of productivity.
[0027] Nb may be added by a method in which a coating liquid containing a water-dispersible sol of a metal salt, or an oxide or hydroxide of La or Ni is applied in advance, dried, and pre-baked, and then a coating liquid containing a water-dispersible sol of a metal salt, oxide, or hydroxide of Nb is applied to the electrode in a topcoat manner, dried, pre-baked, and finally baked. Nb may also be added by a method in which a coating liquid containing a water-dispersible sol of a metal salt, oxide, or hydroxide of La or Ni is applied in advance, followed by drying, pre-baking, and main baking, and then a coating liquid containing a water-dispersible sol of a metal salt, oxide, or hydroxide of Nb is applied to the electrode in a topcoat manner, followed by drying, pre-baking, and main baking.
[0028] (electrolytic cell) FIG. 1 shows a side view of an example of an entire electrolytic cell including an electrolytic cell equipped with the electrode of this embodiment as an anode. FIG. 2 shows a diagram of a zero gap structure of an example of an electrolytic cell including an electrolytic cell equipped with the electrode of this embodiment as an anode (a cross-sectional view of the part enclosed by the dashed square frame shown in FIG. 1). In the bipolar electrolytic cell 50 of this embodiment (see FIG. 3), the diaphragm 4 is in contact with the anode 2a and the cathode 2c to form a zero-gap structure Z (see FIG. 2). An outline of the electrolysis device used in the examples and comparative examples is shown in Fig. 3. Fig. 4 shows an outline of the bipolar electrolysis cell used in the electrolysis tests.
[0029] (element) As shown in FIG. 1, in a bipolar electrolytic cell 50, a bipolar element 60 is disposed between an anode terminal element 51a and a cathode terminal element 51c, and diaphragms 4 are disposed between the anode terminal element 51a and the bipolar element 60, between adjacent bipolar elements 60, and between the bipolar element 60 and the cathode terminal element 51c. In this embodiment, in particular, the portion between the partition walls 1 between two adjacent bipolar elements 60 and the portion between the partition walls 1 between the adjacent bipolar element 60 and the terminal element in the bipolar electrolytic cell 50 are referred to as the electrolytic cell 65. The electrolytic cell 65 includes the partition wall 1, anode chamber 5a, anode 2a, and diaphragm 4 of one element, and the cathode 2c, cathode chamber 5c, and partition wall 1 of the other element.
[0030] (electrode chamber) 2, in the bipolar electrolytic cell 50 of this embodiment, an electrode chamber 5 through which the electrolytic solution passes is defined by the partition wall 1, the outer frame 3, and the diaphragm 4. Here, the electrode chamber 5 on the anode side across the partition wall 1 is the anode chamber 5a, and the electrode chamber 5 on the cathode side is the cathode chamber 5c. In this embodiment, the header pipe of the bipolar electrolytic cell may be of an internal header type or an external header type, and the space occupied by the anode and cathode themselves may be considered to be the space inside the electrode chamber. In particular, when a gas-liquid separation box is provided, the space occupied by the gas-liquid separation box may be considered to be the space inside the electrode chamber.
[0031] (rib) In the bipolar electrolytic cell 65 for alkaline water electrolysis of this embodiment, the rib 6 is preferably physically connected to the electrode 2. With such a configuration, the rib 6 serves as a support for the electrode 2, making it easy to maintain the zero gap structure Z. Furthermore, the rib 6 is preferably electrically connected to the partition wall 1. Furthermore, the provision of the rib 6 can reduce convection that occurs in the electrode chamber 5 due to turbulence in the gas-liquid flow in the electrode chamber 5, thereby suppressing a local increase in the temperature of the electrolyte. Here, an electrode may be provided on the rib, or a current collector, a conductive elastic body, and an electrode may be provided on the rib in this order. In the above-described example of the bipolar electrolytic cell for alkaline water electrolysis, a structure is adopted in which the cathode rib-cathode current collector-conductive elastic body-cathode are stacked in this order in the cathode chamber, and a structure is adopted in which the anode rib-anode are stacked in this order in the anode chamber. In the above-mentioned example of the bipolar electrolytic cell for alkaline water electrolysis, the above-mentioned "cathode rib-cathode current collector-conductive elastic body-cathode" structure is adopted in the cathode chamber, and the above-mentioned "anode rib-anode" structure is adopted in the anode chamber; however, the present invention is not limited to this structure, and an "anode rib-anode current collector-conductive elastic body-anode" structure may also be adopted in the anode chamber. In particular, in the bipolar electrolytic cell for alkaline water electrolysis of the present embodiment, ribs 6 (anode ribs, cathode ribs) are preferably attached to the partition wall 1 as shown in FIG. It is preferable that the ribs (anode ribs, cathode ribs) not only have a role of supporting the anode or cathode but also a role of transmitting current from the partition wall to the anode or cathode. In the bipolar electrolytic cell for alkaline water electrolysis of the present embodiment, it is preferable that at least a part of the rib is conductive, and it is more preferable that the entire rib is conductive. With such a configuration, an increase in cell voltage due to electrode deflection can be suppressed. The material of the rib is generally a conductive metal, such as nickel-plated mild steel, stainless steel, nickel, etc. The material of the rib is preferably the same as that of the partition wall, and most preferably nickel. The distance between adjacent anode ribs or the distance between adjacent cathode ribs is determined taking into consideration the electrolysis pressure and the pressure difference between the anode chamber and the cathode chamber, etc. If the interval between the anode ribs or the interval between the adjacent cathode ribs is too narrow, not only the flow of the electrolyte or gas is hindered, but also the cost is increased. If the rib pitch is 10 mm or more, gas escape to the back surface of the electrode is good. If the rib pitch is too wide, the electrodes (anode and cathode) held by the slight pressure difference between the anode chamber and the cathode chamber are deformed, and the number of anode ribs and cathode ribs is reduced, which increases the electrical resistance. If the rib pitch is 150 mm or less, the electrodes are less likely to bend. The number of ribs, the length of the rib, the angle between the rib and the partition wall, the number of through holes, and the interval (pitch) of the through holes in a given direction along the partition wall may be appropriately determined as long as the effects of the present invention are obtained. The ribs are preferably provided parallel to a given direction along the partition wall (for example, the vertical direction may be set, or the same direction as the direction of one of two pairs of opposing sides when the partition wall has a substantially rectangular shape in plan view). The rib pitch of the anode rib and the rib pitch of the cathode rib may be the same or different, and it is preferable that the rib pitch of the anode rib and the rib pitch of the cathode rib both satisfy the above range. The anode ribs and cathode ribs are attached to the bulkhead by laser welding or the like. The thickness of the rib may be from 0.5 mm to 5 mm, taking into consideration cost, ease of production, strength, etc., and is not particularly limited to 1 mm to 2 mm. The electrodes and current collectors are usually attached to the ribs by spot welding, but other methods such as laser welding may also be used, or they may be tied together with a wire or string-like member for close contact. The ribs are fixed to the partition wall by spot welding, laser welding, or other means, in the same manner as the anode and cathode.
[0032] (Hydrogen production method) Next, a method for producing hydrogen by alkaline water electrolysis using the bipolar electrolytic cell of this embodiment will be described. In this embodiment, hydrogen is produced at the cathode by applying a current to a bipolar electrolytic cell having an anode and a cathode as described above and circulating an electrolyte, thereby performing water electrolysis. In this case, for example, a variable power supply can be used as the power supply. A variable power supply is a power supply derived from a renewable energy power plant whose output fluctuates in units of a few seconds to a few minutes, unlike a power supply that provides a stable output, such as grid power. The method of generating renewable energy is not particularly limited, but examples include solar power generation and wind power generation. For example, in the case of electrolysis using a bipolar electrolytic cell, the cationic electrolyte in the electrolytic solution moves from the anode chamber of an element through the diaphragm to the cathode chamber of an adjacent element, and the anionic electrolyte moves from the cathode chamber of an element through the diaphragm to the anode chamber of the adjacent element. Thus, the current during electrolysis flows in the direction in which the elements are connected in series. That is, the current flows from the anode chamber of one element to the cathode chamber of the adjacent element through the diaphragm. As a result of electrolysis, oxygen gas is produced in the anode chamber and hydrogen gas is produced in the cathode chamber. The bipolar electrolytic cell 65 for alkaline water electrolysis of this embodiment can be used in the bipolar electrolytic cell 50, the electrolytic device 70 for alkaline water electrolysis, etc. An example of the electrolytic device 70 for alkaline water electrolysis includes an apparatus including the bipolar electrolytic cell 50 of this embodiment, a liquid delivery pump 71 for circulating the electrolytic solution, a gas-liquid separation tank 72 for separating the electrolytic solution from hydrogen and / or oxygen, and a water supply device for supplying water consumed by electrolysis. The alkaline water electrolysis apparatus may further include a rectifier 74, an oxygen concentration meter 75, a hydrogen concentration meter 76, a flow meter 77, a pressure meter 78, a heat exchanger 79, a pressure control valve 80, and the like. In the alkaline water electrolysis method using the alkaline water electrolysis apparatus, the current density applied to the electrolysis cell is 4 kA / m 2 ~20kA / m 2 Preferably, 6 kA / m 2 ~15kA / m 2 It is even more preferable that: The electrodes, electrolytic cells, and hydrogen production methods according to the embodiments of the present invention have been illustrated and described above with reference to the drawings. However, the electrodes, electrolytic cells, and hydrogen production methods according to the present invention are not limited to the above examples, and appropriate modifications can be made to the above embodiments. EXAMPLES
[0033] Example 1 Add Ni(NO 3 ) 2 6H 2 O 23.26g, La(NO 3 ) 3 6H 2 34.64 g of O and 30.03 g of glycine were dissolved to prepare the coating solution of Example 1. Thereafter, this coating solution was transferred to a polyethylene container having a base of 13 cm×13 cm and a height of 10 cm. A nickel expand metal with SW 3.0 mm, LW 4.5 mm, thickness 1.2 mm, and aperture ratio 54% was prepared as a nickel porous substrate. After blasting treatment was performed on this nickel expand metal using #80 white fused alumina abrasive, a substrate with a length of 10 cm and a width of 10 cm was cut out, which was acid-treated in 6N hydrochloric acid at 50°C for 6 hours, washed with water, dried, and used as a substrate for coating. The substrate was slowly placed at an angle into the coating solution in the container while stirring the coating solution, and was completely immersed and held for 5 seconds. The substrate was then pulled out, turned vertically, and the excess coating solution was blown off by air blowing with an air gun. The substrate was then dried at 60°C for 10 minutes and baked at 400°C for 10 minutes to form a metal oxide layer on the substrate surface. This cycle of coating, drying and firing was repeated 65 times. When the substrate was placed in the coating solution in the container, it was slowly placed at an angle so that the voids in the metal oxide layer were completely replaced with the coating solution. After that, it was further fired at 800°C for 1 hour, and a coating weight of 250 g / m2 was obtained on the substrate for coating. 2 Thus, a water electrolysis anode of Example 1 was obtained.
[0034] Example 2 Liquids A and B were prepared having the composition of Example 2 in Table 1. Liquid B was prepared by dissolving ammonium niobium oxalate in pure water, and the Nb concentration was confirmed by ICP-AES (inductively coupled plasma atomic emission spectrometry). Solution A was placed in a rectangular polyethylene container measuring 6 cm x 10 cm and 11 cm in height, and solution B was slowly mixed in while stirring with a magnetic stirrer to prepare a coating solution for Example 2. A substrate for coating was prepared in the same manner as in Example 1, and while stirring the coating liquid, the substrate for coating was vertically oriented, and the lower half was slowly immersed in the coating liquid and held for 5 seconds. The substrate was then pulled up, the substrate was turned upside down, and the upper half was also slowly immersed in the coating liquid and held for 5 seconds. After the coating liquid was applied to the entire substrate, the substrate was kept vertically oriented and the excess coating liquid was blown off by air blowing with an air gun. The substrate was then dried at 60°C for 10 minutes and further baked at 400°C for 10 minutes to form a metal oxide layer on the substrate surface. This cycle of coating, drying and baking was repeated 60 times. The substrate was slowly placed in the coating solution in the container so that the voids in the metal oxide layer were completely replaced with the coating solution. The substrate was then baked at 800°C for 1 hour, resulting in a coating weight of 200 g / m2 on the substrate. 2 Thus, a water electrolysis anode of Example 2 was obtained.
[0035] Example 3 The procedure of Example 2 was repeated except that solutions A and B having the compositions of Example 3 in Table 1 were prepared, and a coating weight of 200 g / m was applied to the substrate. 2 Thus, a water electrolysis anode of Example 3 was obtained.
[0036] Example 4 Liquids A and B having the compositions of Example 4 in Table 1 were prepared, and the cycle of drying and baking was repeated 55 times, and then baking was performed at 750°C for 1 hour. The same procedure was followed as in Example 2, and a coating weight of 200 g / m was obtained on the coating substrate. 2 Thus, a water electrolysis anode of Example 4 was obtained.
[0037] Example 5 The procedure was the same as in Example 4, except that solutions A and B having the compositions of Example 5 in Table 1 were prepared, and a coating amount of 200 g / m was applied to the substrate. 2 A metal oxide layer was formed on the anode of Example 5 for water electrolysis.
[0038] Example 6 As in Example 1, the cycle of drying and baking was repeated 70 times. Ammonium niobium oxalate was dissolved in pure water to prepare an aqueous solution of ammonium niobium oxalate with a Nb concentration of 81.4 mmol / kg. This aqueous solution of ammonium niobium oxalate was transferred to a polyethylene container with a base of 13 cm x 13 cm and a height of 10 cm. The substrate with a metal oxide layer formed on its surface was completely immersed in an aqueous solution of ammonium niobium oxalate and then pulled out. After the coating solution was applied to the entire surface of the substrate, the substrate was turned sideways and a weak breeze was applied from an air gun to remove the coating solution that had clogged the substrate. When the weight of the substrate was measured after the air gun treatment, it was found that 1.3 g of the aqueous solution of ammonium niobium oxalate had been applied to the substrate. 3 The amount of LaNiO supported on the substrate was 2.6 g. 3Since the weight of 1 mole of is 245.6 g, the coating of 1.3 g of ammonium niobium oxalate solution with a Nb concentration of 81.4 mmol / kg resulted in LaNiO 3 It was found that 0.01 mole of Nb was applied per mole of Nb. The substrate coated with the aqueous solution of ammonium niobium oxalate was dried at 60°C for 10 minutes, then baked at 400°C for 10 minutes and further baked at 800°C for 1 hour, resulting in a coating weight of 261 g / m 2 Thus, a water electrolysis anode of Example 6 was obtained.
[0039] Example 7 The cycle of drying and firing was repeated 75 times in the same manner as in Example 1. Then, firing was further carried out at 800° C. for 1 hour. Ammonium niobium oxalate was dissolved in pure water to prepare an aqueous solution of ammonium niobium oxalate with a Nb concentration of 187 mmol / kg. This aqueous solution of ammonium niobium oxalate was transferred to a polyethylene container with a base of 13 cm x 13 cm and a height of 10 cm. Thereafter, 1.3 g of an aqueous solution of ammonium niobium oxalate was applied to the substrate in the same manner as in Example 6. 3 The amount of LaNiO supported on the substrate was 2.8 g. 3 Since the weight of 1 mole of is 245.6 g, the coating of 1.3 g of ammonium niobium oxalate solution with a Nb concentration of 187 mmol / kg resulted in LaNiO 3 It was found that 0.02 moles of Nb was applied per mole of Nb. The substrate coated with the aqueous solution of ammonium niobium oxalate was dried at 60°C for 10 minutes, then baked at 400°C for 10 minutes and further baked at 800°C for 1 hour, resulting in a coating weight of 283 g / m 2 Thus, a water electrolysis anode of Example 7 was obtained.
[0040] Example 8 As in Example 1, the cycle of drying and baking was repeated 80 times. In addition, Nb 2 O 5The sol was diluted to obtain Nb with a Nb concentration of 400 mmol / kg sol. 2 O 5 A sol was prepared. This Nb 2 O 5 The sol was applied to both sides of the substrate using a spray coater (RCoater, sold by Asahi Sunac Corporation) and then dried at 60°C for 10 minutes. The weight increase relative to the substrate before application was calculated to be 81 mg. 3 The amount of LaNiO supported on the substrate was 3.0 g. 3 The weight of one mole of Nb is 245.6g. 2 O 5 Since the weight of 1 mole of Nb is 265.2g, 81mg of Nb 2 O 5 By applying LaNiO 3 It was found that 0.05 moles of Nb was applied per mole of Nb. The substrate was dried at 60℃ for 10 minutes, baked at 400℃ for 10 minutes, and then baked at 800℃ for 1 hour to obtain a coating weight of 308g / m 2 Thus, a water electrolysis anode of Example 8 was obtained.
[0041] Example 9 The same procedure as in Example 2 was carried out except that liquids A and B having the composition of Example 9 in Table 1 were prepared and then baked at 750°C for 1 hour. The coating amount on the coating substrate was 200 g / m 2 Thus, a water electrolysis anode of Example 9 was obtained.
[0042] Example 10 Liquids A and B having the composition of Example 10 in Table 1 were prepared, and the procedure was the same as in Example 2 except that they were baked at 750°C for 1 hour. The coating amount on the coating substrate was 200 g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis of Example 10.
[0043] Comparative Example 1 A nickel expand metal with SW 3.0 mm, LW 4.5 mm, thickness 1.2 mm, and aperture ratio 54% was prepared as a nickel porous substrate. This nickel expand metal was roughly blasted using #30 white fused alumina abrasive, then acid-treated in 6N hydrochloric acid at 50°C for 6 hours, washed with water, and dried to prepare a substrate for coating. Next, a coating solution was prepared by mixing lanthanum acetate 1.5-hydrate and nickel nitrate hexahydrate to have concentrations of 0.20 mol / L and 0.20 mol / L, respectively. A vat containing the above coating liquid was placed at the bottom of the coating roll, the coating liquid was soaked into an EPDM coating roll, a roll was placed above it so that the roll and the coating liquid were always in contact, and a PVC roller was placed on top of that to apply the coating liquid to the substrate (roll method). The substrate was quickly passed between two EPDM sponge rolls before the coating liquid dried. After that, it was dried at 50°C for 10 minutes, and then baked at 400°C for 10 minutes in a muffle furnace to form a metal oxide layer on the substrate surface. This cycle of roll coating, drying and baking was repeated 75 times, and then baking was performed at 600°C for 1 hour, resulting in a coating weight of 303 g / m 2 A metal oxide layer of the above was formed to obtain an anode for water electrolysis.
[0044] Comparative Example 2 A substrate for application was prepared in the same manner as in Comparative Example 1. Next, coating solutions were prepared so that lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, ammonium niobium oxalate n-hydrate, and glycine had concentrations of 0.20 mol / L, 0.16 mol / L, 0.04 mol / L, and 0.36 mol / L, respectively. As in Comparative Example 1, the cycle of roll coating, drying and firing was repeated 40 times by the roll method, and then firing was further carried out at 700°C for 1 hour to form a metal oxide layer, with a coating weight of 145 g / m 2 Thus, an anode for water electrolysis was obtained.
[0045] (Metal oxide layer thickness measurement) A small piece of the prepared water electrolysis anode was embedded in epoxy resin, and then a cut surface was prepared, and the cut surface was processed at an acceleration voltage of 6 kV using a broad irradiated BIB processing device argon ion beam (Hitachi High-Technologies Corporation "E3500") The cut surface of the anode to be observed was parallel to the expanded metal strand and passed through the center of the strand. The cut surface was observed with an electron microscope ("S4800" manufactured by Hitachi High-Technologies Corporation), and the thickness of the metal oxide layer was measured at five points, and the average value of the measured values was calculated as the thickness of the metal oxide layer. The measurement results in Examples 1 to 8 and Comparative Examples 1 and 2 are shown in Table 2.
[0046] (Calculation of the ratio (extension length from one end of the interface to the other end) / (straight-line distance from one end of the interface to the other end)) The cut surface was observed with an electron microscope (Hitachi High-Technologies Corporation "S4800") at an accelerating voltage of 5 kV and a magnification of 500 times, and the cross-sectional image of the backscattered electrons taken with a YAG detector was saved as a BMP file with a data size of 1280 x 960 pixels. The size of one pixel was 198.4375 nm. The cross-sectional image was taken and saved while avoiding the peaks (convex parts) and valleys (concave parts) of the bent parts of the substrate. The ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) was calculated using the image processing software "ImageJ" according to the following procedure. The measurement results in Examples 1 to 8 and Comparative Examples 1 and 2 are shown in Table 2. 1) Open the BMP file of the cross-sectional image and select 8-bit in the Type submenu of the Image menu. Figure 5 shows an example of a cross-sectional image. 2) In the Set scale submenu of the Analyze menu, set Distance in Pixels: 1, Known distance: 198.4375, Pixel aspect ratio: 1.0, Unit of length: nm, and click OK. 3) In the Selection submenu of the Edit menu, select the Specify command, check the Scaled units (nm) checkbox, set Width: 100000, Height: 100000, set the X coordinate and Y coordinate values appropriately, and click OK to set a 100 μm square region from which the interface will be extracted from the cross-sectional image. The 100 μm square region from which the interface will be extracted should be set so that the interface is connected from the right end to the left end within the region and is never interrupted by the top, bottom, left, or right ends of the set area. 4) Execute the Crop command in the Image menu to cut out a 100 μm square region from which to extract the interface. Figure 6 shows an example of a 100 μm square region cut out from Figure 5. 5) In the Filters submenu of the Process menu, select Median..., set Radius:4, and click OK to process the filters. 6) From the Plugins menu, select the Multi Otsu Threshold plugin, set numLevels to 3, and click OK. 7) Select Region2, select Median... from the Filters submenu of the Process menu, set Radius:4, and click OK to perform filtering. Select Median... from the Filters submenu of the Process menu again, set Radius:4, and click OK to perform filtering a second time. 8) Execute the Find Edges command in the Process menu. 9) From the Image menu, select the Threshold command in the Adjust submenu, check the Dark background check box, and click Apply. 10) Select the skeletonize command from the Binary submenu of the Process menu to thin the interface. Figure 7 shows an example of an image in which the interface has been extracted from Figure 6 and thinned. 11) From the Plugins menu, select the BoneJ plugin, select Analyze skeleton, check the Calculate largest shortest path checkbox, check the Show detailed info checkbox, and click OK. 12) In the Branch information window, the data in the row of the Skeleton ID with the largest value in the Branch length column is the data of the extracted interface. The Branch length in the data in the row of that Skeleton ID is the extension length from one end of the interface to the other (nm), and the Euclidean distance is the linear distance from one end of the interface to the other (nm). The Branch length is divided by the Euclidean distance to calculate the ratio (extension length from one end of the interface to the other) / (linear distance from one end of the interface to the other). Figure 8 shows an image of the extension length from one end of the interface, and Figure 9 shows an image of the linear distance from one end of the interface to the other.
[0047] (How to make a zero-gap electrolytic cell anode with 500 hours of current) An electrolytic cell for alkaline water electrolysis and a bipolar electrolytic cell were prepared as follows. -anode- The anodes of Examples 1 to 8 and Comparative Examples 1 and 2 were used. -cathode- The conductive substrate used was a plain weave mesh substrate made of nickel thin wires with a diameter of 0.15 mm woven at 40 meshes, on which platinum was supported. -Partition walls, outer frames- The bipolar element used had a partition wall separating the anode and cathode and an outer frame surrounding the partition wall. All of the materials of the members that come into contact with the electrolyte, such as the partition wall and the frame of the bipolar element, were made of nickel. -Conductive elastic body- The conductive elastic body used was made by weaving nickel wire with a wire diameter of 0.15 mm and corrugating it to a wave height of 5 mm. -diaphragm- A coating solution having the following component composition was obtained using zirconium oxide (product name "EP Zirconium Oxide", manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.), N-methyl-2-pyrrolidone (manufactured by Wako Pure Chemical Industries, Ltd.), polysulfone ("Udel" (registered trademark), manufactured by Solvay Advanced Polymers), and polyvinylpyrrolidone (weight average molecular weight (Mw) 900,000, manufactured by Wako Pure Chemical Industries, Ltd.). Polysulfone: 15 parts by weight Polyvinylpyrrolidone: 6 parts by weight N-methyl-2-pyrrolidone: 70 parts by weight Zirconium oxide: 45 parts by mass The above coating liquid was applied to both surfaces of a substrate, a polyphenylene sulfide mesh (manufactured by Kureha Co., Ltd., film thickness 280 μm, mesh size 358 μm, fiber diameter 150 μm). Immediately after coating, the substrate coated with the coating liquid was exposed to steam, and then immersed in a coagulation bath to form a coating film on the substrate surface. The coating film was then thoroughly washed with pure water to obtain a porous film. -gasket- The gasket used was a square with an inner dimension of 504 mm square, 4.0 mm thick and 18 mm wide, with an opening on the inside that was the same dimensions as the electrode chamber in a plan view, and a slit structure for inserting and holding the diaphragm. -Zero gap type multi-pole element- The external header type zero gap cell unit 60 is a rectangle of 540 mm x 620 mm, and the area of the current-carrying surface of the anode 2a and cathode 2c is 500 mm x 500 mm. The cathode side of the zero gap type bipolar element 60 has a cathode chamber 5c in which the cathode 2c, conductive elastomer 2e, and cathode current collector 2r are laminated and connected to the partition wall 1 via the cathode rib 6, and an electrolyte flows. The anode side has an anode chamber 5a in which the anode 2a is connected to the partition wall 1 via the anode rib 6, and an electrolyte flows (Fig. 2). The depth of the anode chamber 5a (anode chamber depth, the distance between the partition wall and the anode in FIG. 2) was 25 mm, and the depth of the cathode chamber 5c (cathode chamber depth, the distance between the partition wall and the cathode current collector in FIG. 2) was 25 mm, and the material was nickel. The thickness of the nickel partition wall 1 to which the nickel anode rib 6 with a height of 25 mm and a thickness of 1.5 mm and the nickel cathode rib 6 with a height of 25 mm and a thickness of 1.5 mm were attached by welding was 2 mm. A nickel expand base material that had been blasted in advance was used as the cathode current collector 2r. The base material had a thickness of 1 mm and an aperture ratio of 54%. The conductive elastic body 2e was fixed onto the cathode current collector 2r by spot welding. By stacking this zero-gap type bipolar element via a gasket that holds the diaphragm, a zero-gap structure Z in which the anode 2a and the cathode 2c are pressed against the diaphragm 4 can be formed. Using the above electrolysis device, the electrolyte temperature was adjusted to 80°C, and the current density was 10 kA / m 2 A positive current was continuously applied for 300 hours to perform water electrolysis so that the electrolyte was removed from the electrolytic cell, the alkali in the electrolytic cell was washed with pure water, the electrolytic cell was removed from the frame, the anode was taken out and dried, and anodes of Examples 1 to 8 and Comparative Examples 1 and 2 were prepared by applying a current for 500 hours in a zero-gap type electrolytic cell.
[0048] (Measurement of oxygen overvoltage of anode of zero-gap electrolytic cell with current applied for 500 hours) The oxygen overvoltage of the zero-gap type electrolytic cell was measured by passing a current through the anode for 500 hours as follows. An electrode measuring 2 cm x 2 cm was cut out from the anode of the zero-gap electrolytic cell, which had been energized for 500 hours, and fixed to a nickel rod coated with PTFE with a nickel screw. A platinum mesh was used as the counter electrode, and the current density was 6 kA / m in a 32 wt% sodium hydroxide aqueous solution at 80°C. 2The electrolyte was electrolyzed with 0.1% NaCl and the oxygen overvoltage was measured. The oxygen overvoltage was measured by the three-electrode method using a Luggin capillary in order to eliminate the effect of ohmic loss due to the electrolyte resistance. The distance between the tip of the Luggin capillary and the anode was always fixed at 1 mm. The device used to measure the oxygen overvoltage was a Solartron potentiogalvanostat "1470E System." Silver-silver chloride (Ag / AgCl) was used as the reference electrode for the three-electrode method. The electrolyte resistance that could not be completely eliminated by the three-electrode method was measured by the AC impedance method, and the oxygen overvoltage was corrected based on the measured electrolyte resistance. A Solartron frequency response analyzer “1255B” was used to obtain a Cole-Cole plot of the real and imaginary parts, and the electrolyte resistance and double layer capacitance were calculated by analyzing the plot using equivalent circuit fitting. The ohmic loss that could not be completely eliminated by the three-electrode method was measured by the AC impedance method, and the oxygen overvoltage was corrected based on the measured ohmic loss. The frequency characteristic analyzer "1255B" manufactured by Solartron was used to measure the ohmic loss. The evaluation results for Examples 1 to 8 and Comparative Examples 1 and 2 are shown in Table 2.
[0049] [Table 1]
[0050] [Table 2] [Industrial Applicability]
[0051] INDUSTRIAL APPLICABILITY The electrode of the present invention has a low overvoltage for oxygen generation after current recovery in a zero-gap electrolytic cell, and can therefore be suitably used as an anode of a reusable water electrolytic cell in the electrolysis of alkali-containing water. [Explanation of symbols]
[0052] 1 Bulkhead 2 electrodes 2a anode 2c cathode 2e Conductive elastic body 2r Cathode current collector 3 Outer frame 4 Diaphragm 5a Anode chamber 5c cathode chamber 6. Ribs 7 Gasket 50 bipolar electrolyzer 51g fast head, loose head 51i Insulating plate 51a Anode terminal element 51c Cathode Terminal Element 51r tie rod 60 Multi-pole element 65 Electrolysis Cell 70 Electrolyzer 71 Liquid delivery pump 72 Gas-liquid separation tank 74 Rectifier 75 Oxygen concentration meter 76 Hydrogen concentration meter 77 Flow meter 78 Pressure Gauge 79 Heat exchanger 80 Pressure Control Valve Z Zero gap structure
Claims
1. On a nickel substrate, LaNi x Nb y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0 or more and 0.2 or less, z is -0.5 or more and 0.5 or less), and the nickel base material and LaNi x Nb y O 3-z 1. An electrode, characterized in that at an interface between said layer and said electrode, a ratio of (extension length from one end of said interface to the other end) / (linear distance from one end of said interface to the other end) is 1.5 or more and 3 or less.
2. The LaNi x Nb y O 3-z 2. The electrode of claim 1, wherein the layer has a thickness of 60 μm to 100 μm.
3. 3. The electrode according to claim 1, wherein y is 0.001 or more and 0.15 or less.
4. 4. An electrolytic cell comprising the electrode according to claim 1 as an anode.
5. In a method for producing hydrogen by electrolyzing water containing an alkali in an electrolytic cell, the electrolytic cell is provided with at least an anode and a cathode, and the anode is provided with a LaNi x Nb y O 3-z (x+y is 0.8 or more and 1.2 or less, y is 0 or more and 0.2 or less, z is -0.5 or more and 0.5 or less), and the nickel base material and LaNi x Nb y O 3-z A method for producing hydrogen, characterized in that at an interface between layers, a ratio of (extension length from one end of the interface to the other end) / (linear distance from one end of the interface to the other end) is 1.5 or more and 3 or less.
Citation Information
Patent Citations
Anode for alkali water electrolysis and manufacturing method of anode for alkali water electrolysis
JP2017190476A
Diaphragm, electrolytic bath, and hydrogen manufacturing method
JP2019183252A
Electrochemical Methods and Systems Using Catalytic Materials
US20130020207A1
Electrolytic bath, electrolysis device, electrolysis method, and method for producing hydrogen
WO2018139616A1
Positive electrode, positive electrode for water electrolysis, electrolysis cell, and method for producing hydrogen
WO2018155503A1